STARM: Environmental Data Time Series of the Magallanes and Chilean Antarctic Region ... : STARM: Series de tiempo ambientales para la Región de Magalles y la Antártica Chilena ... - Data Observatory; IDEAL; Universidad Austral de Chile (Data Observatory, 2022)
Environmental Data Time Series of the Magallanes and Chilean Antarctic Region (STARM), was developed as a technology transfer product of the research carried out by the IDEAL center. STARM aims to make available to the national and international community the information provided by the platforms (moorings, cruises, meteorological stations and FerryBox) installed in different stations or vessels in the Magallanes Region and Antarctic peninsula. FerryBox is funded by the FONDEQUIP program (Fund for Scientific and Technological Equipment) project EQM 190013. ...